Phosphate-solubilizing and polymerizing bacteria enhance phosphorus availability and growth of rice - Yang, Meiying; Qin, Xueting; Yue, Chengcai; Wu, Qi; Tian, Ping; Wu, Zhihai; Wei, Xiaoshuang; Wu, Lei (Frontiers in Microbiology, 2025)
IntroductionPhosphorus (P) is a limiting nutrient in soil-plant nutrient cycling, functional microorganisms can promote P transformation. While previous studies have mainly focused on either phosphorus solubilization or phosphorus aggregation by bacterial strains, few address both aspects simultaneously.MethodsIn this study, we screened Acinetobacter johnsonii (NHP4a-2) and Pseudomonas glycinae (NHP4b-2) strains, both of which can effectively solubilize and polymerize P. Their performance was evaluated by measuring phosphate solubilization capacity, polyphosphate accumulation levels, and the activity of related enzymes (polyphosphate kinase, extrapolyphosphatase, and glucose dehydrogenase). A high-phosphorus/low-phosphorus alternating culture system was employed to simulate aerobic-anaerobic cycles, monitoring phosphorus uptake and release dynamics. Transcriptomic analysis revealed the molecular mechanisms underlying their phosphorus solubilization, and their growth-promoting effects were validated through rice pot experiments.ResultsThe phosphorus solubilization capacity of NHP4a-2 is 33% that of NHP4b-2. Under alternating high- and low-phosphorus conditions, the aerobic phosphorus uptake and anaerobic phosphorus release functions of the two bacterial strains. In addition, the polyphosphate kinase, Exopolyphosphatase, and Glucose dehydrogenase enzyme activities of strain NHP4b-2 were higher than those of strain NHP4a-2. Transcriptome analyses show that NHP4b-2 exhibited significant upregulation of 93 differentially expressed genes and downregulation of 264 differentially expressed genes under phosphate solubilization conditions. ATP metabolism, oxidative phosphorylation, and glycolysis/gluconeogenesis pathways supply ATP and acidic compounds to the strain, thereby supporting its phosphate solubilization function. NHP4b-2 exhibits stronger polyphosphate accumulation capabilities than NHP4a-2. This strain absorbs and stores increasing amounts of phosphorus as phosphorus concentration rises. Under low-phosphorus conditions, it releases phosphorus to support plant growth. Compared with the NHP4a-2 treatment group, the NHP4b-2 treatment group exhibited increases of 6.3, 26.3, 13.3, 25.4, and 56.9% in rice seedling plant height, root length, fresh leaf weight, fresh root weight, and phosphorus content, respectively, positively impacting the growth of the rice seedlings.DiscussionThe results of this study indicate that strains possessing both high-efficiency phosphorus solubilization and phosphorus accumulation capabilities achieve effective phosphorus activation and storage by regulating key metabolic pathways, significantly promoting plant phosphorus uptake and growth. This study provides valuable insights into sustainable phosphorus management in agriculture and may have future applications in various agricultural settings.